HUBUNGAN STATUS GIZI DENGAN KEJADIAN PIODERMA PADA BALITA DI DESA KUOK - Siska Indriyani; Alini Alini (Universitas Pahlawan, 2020)
Children under the age of five or under five are a group that is prone to nutrition, because they are prone to malnutrition due to lack of food needed. Malnutrition in children will cause decreased immunity, which means that the ability to defend themselves against bacterial infection decreases. Children who have less nutritional status have the potential to suffer from pyoderma. Lack of the amount of food consumed both in quality and quantity can reduce the nutritional status of children. The purpose of this study was to determine the relationship between nutritional status and the incidence of pyoderma in toddlers (1-5 years) in Kuok Village, the working area of Puskesmas Kuok in 2020. This study used an analytical research design with a case control design. The sample in this study were 62 children (1-5 years). 31 samples for the case group and 31 samples for the control group. data collection through questionnaires. Data processing used univariate and bivariate analysis with the Chi-Square test. The results showed that there was a significant relationship between nutritional status and the incidence of pyoderma in toddlers (1-5 years) with p value = 0.001. By holding this research, the researchers expected parents of toddlers to pay more attention to the nutritional status of their children in order to avoid infectious diseases such as pyoderma.